Genetic association analysis of inositol polyphosphate phosphatase-like 1 (INPPL1, SHIP2) variants with essential hypertension. Issue 9 (8th June 2007) - Marçano, Ana Carolina Braga; Burke, Beverley; Gungadoo, Johannie; Wallace, Chris; Kaisaki, Pamela J; Woon, Peng Y; Farrall, Martin; Clayton, David; Brown, Morris; Dominiczak, Anna; Connell, John M; Webster, John; et al.
Abstract : Background: Inositol polyphosphate phosphatase-like 1 ( INPPL1, SHIP2 ) is a negative regulator of insulin signalling and has previously been found to be associated with hypertension, obesity and type 2 diabetes in a cohort of families with diabetes in the UK presenting features of metabolic syndrome. In particular, a haplotype of three genetic polymorphisms (rs2276047, rs9886 and an insertion/deletion polymorphism in intron 1) was found to be strongly associated with increased susceptibility to hypertension. Objective and methods: To assess if INPPL1 variants play a direct role in the development of essential hypertension, we genotyped the three previously associated INPPL1 polymorphisms in a cohort of 712 families with severe hypertension from the BRIGHT study transmission disequilibrium test cohort. Results: We found no evidence of significant association between hypertension and any of the three INPPL1 polymorphisms or haplotypes (p>0.1). Conclusion: These results suggest that INPPL1 variants may be involved in mechanisms causing hypertension in metabolic syndrome patients specifically.